A study of frustrated system in 2 dimensional triangular lattice antiferromagnet using the Ising model - Noor Rika Safitri; Aini Rahmatun Ummi Fadlilah; Denny Darmawan; Yosi Aprian Sari (Jurnal Sains Dasar, 2013)
Abstract This research was aimed to simulate the ground state and magnetization of antiferromagnet under the influence of temperature and competing interaction. The effect of competing interaction to phase transition was also investigated. The competition occurred between the nearest neighbour interaction and the next nearest neighbour interaction in the triangular lattice. The simulation was done using the 2 dimensions Ising model with Monte Carlo method combined with Metropolis algorithm. The results showed that the ground state energy increased significantly at the critical temperature (Neel’s temperature). When the competing interaction increased, the ground state energy of the lowest temperature decreased. Based on the magnetization, due to the increase of the competing interactions, the phase transitionfrom antiferromagnet to paramagnet occurred at a higher Neel’s temperature.   Key words: antiferromagnet, Ising model, competing interaction, Neel’s temperature